Prostate-specific IL-6 transgene autonomously induce prostate neoplasm through amplifying inflammation in the prostate and peri-prostatic adipose tissue. Issue 1 (December 2017) - Liu, Gang; Zhang, Jinyu; Frey, Lewis; Gang, Xiao; Wu, Kongming; Liu, Qian; Lilly, Michael; Wu, Jennifer
Abstract Background The causative role of the pro-inflammatory cytokine IL-6 in prostate cancer progression has been well established at molecular level. However, whether and how IL-6 may play a role in prostate cancer risk and development is not well defined. One limitation factor to acquiring this knowledge is the lack of appropriate animal models. Methods We generated a novel line of prostate-specific IL-6 transgenic mouse model. We compared the prostate pathology, tumorigenic signaling components, and prostate tumor microenvironment of the IL-6 transgenic mice with wild type littermates. Results With this model, we demonstrate that IL-6 induces prostate neoplasm autonomously. We further demonstrate that transgenic expression of IL-6 in the prostate activates oncogenic pathways, induces autocrine IL-6 secretion and steadily-state of STAT3 activation in the prostate tissue, upregulates paracrine insulin-like growth factor (IGF) signaling axis, reprograms prostate oncogenic gene expression, and more intriguingly, amplifies inflammation in the prostate and peri-prostatic adipose tissue. Conclusions The pro-inflammatory IL-6 is autonomous oncogene for the prostate. IL-6 induces prostate oncogenesis through amplifying local inflammation. We also presented a valuable animal model to study inflammation and prostate cancer development.